Siyasah Syar’iyah Paradigm of Hajj Financial Management Regulation in Indonesia - Zakiruddin, Muhammad Aziz; Kamsi, Kamsi; Bahiej, Ahmad (Institut Agama Islam Negeri Curup, 2022)
The purpose of this study is to describe the policies taken by the government in the financial management of Hajj in Indonesia through the siyasah syar'iyah paradigm. The questions that arise in this study are regarding the role of the state in the management of Hajj finances and how the policies of Hajj financial management in Indonesia are in the perspective of siyasah syar'iyah. This research is a library research, with a normative legal research method that uses the siyasah syar'iyah approach. After conducting in-depth research, it was concluded that the government in this case through the BPKH seeks to carry out its role in the field of the 'ala al-hajj and Maliyah areas by building the management and investment of hajj funds that are in line with the siyasah syar'iyah, so that the policies that have been implemented by the government in managing the hajj funds include: the initial deposits, the efforts to maintain the value of BPIH, as well as the placements in Islamic banks. It is an effort to achieve Maqasid Syariah, namely the values of benefit that are specifically for the Hajj pilgrims and the community in general which are the government's goal in this policy.